A Adsorbent of Chitosan Linked by Methylene Bridge and Schiff Base of 4,4-diaminodiphenyl Ether –vanillin : Synthesis, Characterization and Its Application After Reacted by Zn(II) Ion as Antibacterial Agent - Ahmad Fatoni; Poedji Loekitowati Hariani; Hermansyah Hermansyah; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
The synthesis chitosan linked by methylene bridge-Schiff base of 4,4-diaminodiphenyl ether-vanillin (modified chitosan adsorbent) has been studied. The aims of this research were modification of chitosan with Schiff base of 4,4-diaminodiphenyl ether-vanillin and formaldehyde and its application as antibacterial agent after used as an adsorbent of Zn(II) ion. Characterization of modified chitosan adsorbent was conducted using FTIR spectroscopy. Process of adsorption were conducted at 0.15 g of modified chitosan adsorbent reacted by concentration of Zn(II) ion solution (pH 6, 150 mg/L, 50 mL), contact time at 150 min. and at room temperature (280C). Modified chitosan adsorbent after reacted by Zn(II) ion solution as antibacterial agent with paper disk method. The result showed that chitosan can be modified with Schiff base of 4,4-diaminodiphenyl ether-vanillin and formaldehyde to form chitosan linked methylene bridge and Schiff base of 4,4-diaminodiphenyl ether-vanillin. Antibacterial of chitosan and modified chitosan adsorbent were higher than modified chitosan adsorbent after reacted by Zn(II) ion. Keywords : modified chitosan, antibacterial agent